Effects of vitamin E and selenium on rumen protozoa in lambs - Naziroglu, M; Aksakal, M (Scientific Technical Research Council Turkey, 1997)
The present study was undertaken to determine the effects of selenium and vitamin E on number of rumen protozoa, volatile fatty acids, pH and ammonia nitrogen in rumen content. Twelve lambs were used and divided randomly into three groups. One group was used as control. Second group was fed with vitamin E (DL-alpha tocopheryl acetyl, 250 mg/kg feed) and third group was fed with selenium (Sodium selenit, 0.3 mg/kg feed) supplemented diet. Rumen contents of all lambs were obtained three times in the day [before feeding (08.00 hour) and at the 3rd (11.00 hour) and 6th (14.00 hour) hours after feeding] on a weekly basis for ten weeks. in addition, all of lambs were weighed at two weeks intervals. In vitamin E group, levels of acetic, propionic, butyric and total Volatile fatty acids and numbers of total protozoa were statistically higher comparing with those of control group. However, pH values and percentage of Isotricha, Dasytricha ruminantum, Diplodinium were statistically lower in vitamin E group than in control. Ammonia nitrogen levels did not differ between two groups. In selenium group, levels of acetic, propionic, butyric and total volatile fatty acids, numbers of total protozoa and percentage of Diplodinium and ophryoscolex caudatum were statistically higher comparing with those of control group while pH values were higher in control group. In Vitamin E group, butyric acid and levels of total volatile fatty acids and number of total protozoa were statistically lower (P<0.05. P<0.001) compare with selenium group while pH values and percentage of Entodinium caudatum were higher (P<0.05, P<0.01). in addition, percentage of Dasytricha ruminantum, Diplodinium, Ophryoscolex caudatum and Isotrichia were lower in vitamin E group than in selenium group. Weight gain in selenium group was significantly greater than in the others. As result of this experiment. supplementation of selenium and vitamin E to the lambs ration caused an increase in levels of volatile fatty acids. numbers of the total protozoa and a decrease in pH values. However selenium addition only caused to weight gain.
Kuzularda E Vitamini ye Selenyumun Rumen Protozoonlan Üzerine Etkileri
Keywords: vitamin E; selenium; rumen protozoa; volatile fatty acids; ammonia nitrogen